Formation of the information and methodological competence of students in the process of distance learning - Akhmetzhanova, G.A.; Sarbassova, K.A.; Shraimanova, G.S.; Tazhigulova, G.O.; Bukh, R.P. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
The article discusses the issues of distance learning, which has become popular with the advent of the Internet, opening up new development opportunities for residents of remote communities and business people with busy work schedules, is perceived only as an additional way to gain knowledge or prepare for exams, provides an opportunity full-fledged distance courses and advanced training programs at prestigious universities, commercial and non-profit companies from different countries, anywhere in the world, at a convenient time and pacing. Thus, distance education was an important problem for Kazakhstan even before the pandemic, which made the issue even more pressing. The authors also discuss the differences and provide examples of distance and online learning. The essence of online learning and distance learning concepts is revealed. Ways of providing students with information and methodological materials in distance learning are considered. The authors carried out a theoretical and methodological analysis of distance learning, distance education concepts. The paper identifies and analyzes the mechanisms of establishment of distance education. The types of international and national online platforms are shown. For illustrative examples of the resources used, the authors describe “on-screen” copies of the lectures of the online conference program zoom.us and idl.ksu.kz — platforms for distance learning of Karaganda University of the name of academician E.A. Buketov. The paper summarizes the problems of distance education, including the organization of distance learning of the University, outlines the prospects for further scientific developments.
Қашықтықтан оқыту үдерісінде білім алушылардың ақпараттық-әдістемелік құзыреттілігін қалыптастыру
Формирование информационно-методической компетенции обучающихся в процессе дистанционного обучения
Keywords: information technologies; distance education; distance learning; online learning; online platform; information competence; methodical competence; motivation